2020
DOI: 10.3390/w12123308
|View full text |Cite
|
Sign up to set email alerts
|

I2-RED: A Massive Update and Quality Control of the Italian Annual Extreme Rainfall Dataset

Abstract: The collection and management of hydrological data in Italy has been dealt with at national level, initially, by the National Hydrological Service (SIMN), and at regional level in the last 40 years. This change has determined problems in the availability of complete and homogeneous data for the whole country. As of 2020, an updated and quality-controlled dataset of the historical annual maxima rainfall in Italy is still lacking. The Italian Rainfall Extreme Dataset (I-RED) has recently been created to allow st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In this paper, we have analyzed the role of orography and morphology in short-duration annual maximum rainfall depths, taking advantage of a new and comprehensive database for Italy, I 2 -RED (Mazzoglio et al, 2020a). The approach finds its relevance in the first use of the most complete and updated data collection of short-duration annual maxima available for the whole Italian territory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we have analyzed the role of orography and morphology in short-duration annual maximum rainfall depths, taking advantage of a new and comprehensive database for Italy, I 2 -RED (Mazzoglio et al, 2020a). The approach finds its relevance in the first use of the most complete and updated data collection of short-duration annual maxima available for the whole Italian territory.…”
Section: Discussionmentioning
confidence: 99%
“…As the first step of the analysis, we investigated the influence of elevation on the spatial distribution of the average of annual maximum rainfall depths. We calculated the ADD curve parameters for all the stations of the I 2 -RED dataset (Mazzoglio et al, 2020a) to compare them with previous studies (mainly Avanzi et al, 2015). Parameters a and n (cf.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, this relation cannot be generalized to all seasonal periods and it is generally not valid during the summer when thunderstorm convection generally occurs [53]. A confirmation was made by the authors of [54], who carried out a study for the whole Italian Peninsula based on the Improved Italian-Rainfall Extreme Dataset (I2-RED) [62]. These authors have reported that it is rather difficult to find a generalized orographic precipitation gradient, although their analysis has not given any statistical evidence of a correlation between rainfall and elevation for the Italian Peninsula considering extreme rainfall events.…”
Section: Introductionmentioning
confidence: 99%